URGENSI LOGO HALAL PADA PLATFORM MAKANAN DI INDONESIA - Syamsuri, Andi Santri; Ribi, Himawati; AL-Hayyong, Muhammad (RESTORATIVE JOURNAL, 2024)
ABSTRACTThis article describes the importance of halal logos on food exhibitions on e-commerce platforms such as GoFood, GrabFood and ShopeeFood in Indonesia. Through surveys and literature analysis, it was found that the halal logo plays a significant role in building consumer confidence and influencing purchasing decisions. The findings indicate that e-commerce platforms need to display the halal logo clearly to increase consumer confidence and guarantee the validity of the products sold. This descriptive study explains the importance of the halal logo on food sold on the Internet on food platforms so that it can be consumed by Muslims in Indonesia. Qualitative research using research literature refers to the issue and importance of certification or halal logo on food and from the results of previous research related to the problem discussed. This discussion suggests that the halal logo plays an important role in the food e-commerce platform. With increasing consumer awareness and strict regulation, it is important for entrepreneurs to ensure that their products are certified legal and that such information is clearly communicated to consumers. Collaborative efforts between governments, entrepreneurs, and e-commerce platforms are essential to building an ecosystem that supports halal products.Keywords: Urgency, Halal Logo, Food Platform, Indonesia